Analisis ROA, ROE, DER Terhadap Stock Prices (Penelitian Empiris pada Perusahaan yang Tergabung dalam Indeks LQ-45 pada BEI) - Wantah, Feiby Novita; Sukatno, Monika Innercentia Ken; Gazali, Ahmad (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The price of stocks is a key indicator of the health and productivity of businesses, and it also serves as a means of investment for those who wish to make investments. Using the ratios of return on equity, return on asset, and debt to equity, the study's goal is to identify the factors that affect the price of stocks. This study uses companies in LQ45 that are listed on the Indonesian Stock Exchange for the years 2016–2023. This study employs a quantitative approach that is analyzed using a berganda regression using SPSS version 20. 96 companies that met the requirements were used as samples in this study. Purposive sampling was the sampling method used The study's findings indicate that return on equity and return on assets do not significantly affect the price of stocks. Conversely, DER indicates a significant but negative relationship with the stock price, indicating that higher leverage may be interpreted as detrimental by investors because to the potential risk associated with higher utang levels. To put it another way, this study highlights how important it is for businesses to strategically manage its modal structure since it demonstrates how important it is to follow the best possible utang rasio with regard to ekuitas in order to increase market value and investor confidence.